2019
DOI: 10.1001/jamainternmed.2018.7639
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Drivers of Disenrollment and Plan Switching Among Medicare Advantage Beneficiaries

Abstract: IMPORTANCE How often enrollees with complex care needs leave the Medicare Advantage (MA) program and what might drive their decisions remain unknown. OBJECTIVE To characterize trends in switching to and from MA among high-need beneficiaries and to evaluate the drivers of disenrollment decisions. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study of MA and traditional Medicare (TM) enrollees from January 1, 2014, through December 31, 2015, used a multinomial logit regression stratified by Medicare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 41 publications
5
76
3
Order By: Relevance
“…Previous research [25][26][27][28] has found that healthy beneficiaries are more likely to enroll in MA than TM, suggesting that advantageous selection would invalidate a direct comparison between MA and TM beneficiaries. To address selection bias, we used an instrumental variable approach, using county-level MA enrollment rate as an instrument for the individual-level decision to enroll in MA plans.…”
Section: Variablesmentioning
confidence: 99%
“…Previous research [25][26][27][28] has found that healthy beneficiaries are more likely to enroll in MA than TM, suggesting that advantageous selection would invalidate a direct comparison between MA and TM beneficiaries. To address selection bias, we used an instrumental variable approach, using county-level MA enrollment rate as an instrument for the individual-level decision to enroll in MA plans.…”
Section: Variablesmentioning
confidence: 99%
“…Furthermore, MA and TM enrollees are known to differ in important ways 12 and may have different preferences when selecting which hospitals they use for their care needs.…”
Section: Introductionmentioning
confidence: 99%
“…Most Medigap policies eliminate inpatient cost sharing altogether, which is a much larger change than our study and presumably less relevant for Medicare Advantage, purchasing Medigap reduces or eliminates cost sharing for many other services besides inpatient care, and the effect of cost sharing may differ in Medicare Advantage given supply-side, managed care constraints that are not found in traditional Medicare. Recent studies related to Medicare and Medicare Advantage focused on prescription drug use and adherence [12,13], skilled nursing facility utilization [14], or Medicare Advantage enrollment [15]. The lack of inpatient utilization studies in the broader Medicare fee-for-service and Medicare Advantage programs is an important gap since hospital costs are the largest component of Medicare spending and the Medicare Part A deductible is the largest single out-of-pocket expense in the traditional Medicare benefit structure, $1340 in 2018 [16].…”
Section: Introductionmentioning
confidence: 99%